Employing English reading activities to promote English reading comprehension of EFL undergraduate students through self-made teaching materials - Jittisukpong, Pisith; Disa, Teekawin (Kasetsart Journal of Social Sciences, 2026)
The purposes of this study were (1) to construct English reading activities through self-made teaching materials for developing English reading comprehension for first-year undergraduate students at a private university in Bangkok, (2) to compare students’ learning achievement between the pre-test and the post-test of employing English reading activities through self-made teaching materials, and (3) to gauge the students’ level of satisfaction towards activities through self-made teaching materials. Twenty-five students were purposely selected from first-year undergraduate students at a private university in Bangkok during the first semester of the 2023 academic year. The instruments used were five units of English lessons based on general reading content, a reading achievement test, a questionnaire, and an interview to gauge the subjects’ positive assessment of the effectiveness of the instructional materials. The t-test was utilized to analyze the English reading progress of the subjects before and after using the English reading lessons based on general reading content. Data analysis was carried out by examining the questionnaire scores in terms of standard deviation, percentages and mean. The results showed that: (1) English reading activities through self-made teaching materials for developing English reading comprehension had an efficiency of 85.60/82.50, which was higher than the 80/80 standard. (2) There was a significant difference between the pre-test and the post-test at p < .05 the level of significance. (3) The students reported a high level of satisfaction towards English reading lessons.